Tourists’ apprehension toward choosing the next destination: A study based on the learning zone model - Manolicǎ, Adriana; Ionesi, Diana-Sînziana; Drǎgan, Lorin-Mircea; Roman, Teodora; Bertea, Patricia Elena; Boldureanu, Gabriela (Frontiers in Psychology, 2022)
The current research is based on Senninger’s Learning Zone Model applied to the tourists' comfort zone. This model was created in 2000 and it proved to be useful in many applied areas: Psychology, Sociology, Marketing and Management. This modes is a behavioral one and shows how a person can justify his action based on previous tested experiences (comfort zone) or dares to step beyond in fear, learn or growth zone. Our research is extending the existent area of expertise to tourism. We aimed at exploring whether the tourists' apprehension towards choosing their next destination from a comfort zone perspective or rather from the other zones’ perspectives such as fear, learning or growth. To meet this purpose we conducted a mixed method: firstly a qualitative one, an in-depth interview based on Delphi method with 10 tourism specialists and secondly an online survey on 208 Generation Z tourists. The interviews were meant to help developing a 20 items scale (5 items for each level of the model) to measure from which of the 4 zones are the respondents making the choice of the future travel destination. Our conclusions show that Gen Z tourists display behaviors that can be associated with learning or growth zones rather than the comfort zone. This is relevant when choosing the next travel destination, because our findings could bring about a new approach to promoting tourist destinations as part of various products. As a result, a large range of managerial tools can better adapt the promotion messages to the target market from a new psychological perspective.